Simulation Studies of Biomass Gasification System - Hamid, Muhammd Faris (IRC, 2016)
Currently, the need of clean energy are extensively sought after as the world has seen the side effect of harnessing energy derived from the use of fossil fuel. The discovery biomass as an alternive source of renewable energy has changed the “useless-perceptions” towards agricultural waste, forestry residue, urban wood waste and etc. One of the promising method that can change these wastes into value-added product viz biomass gasification. Biomass gasification is a thermochemical conversion process which turn the biomass feedstock into the products equipped with commercial value. It plays an important role in the bioenergy industry. In this paper, a simulation study based on biomass gasification process is going to be done.